Brain vs computer the challenge of the century is now launched - Fillard, J. P. (Singapore : World Scientific, 2020)
"In this follow up to Brain vs Computer: The Challenge of the Century, Jean-Pierre Fillard brings together diverse perspectives to address the recurring theme of rivalry between man and machine. Accelerated by recent events such as the Covid-19 pandemic that caught the world by surprise and brought it to a standstill, the use of technology has become more relevant than ever. What new conclusions can we draw in this debate featuring humans (brain) on the one side, and artificial intelligence (computer) on the other? Featuring brand new content including a complementary perspective from the arts, the author balances the argument from the traditional scientific approach of logic, rationality, and computation with instinct, intuition, and emotion. Read together with his latest offerings Longevity in a 2.0 World and Transhumanism: A Realistic Future? this trilogy culminates in an attempt to answer one of the most exciting questions of our time"--Publisher's website.
About our brain : how does it work?. The biological hardware (hardmeat). The biological software (softmeat). Be aware of consciousness. Transcendence -- Towards an intelligent computer. The origin of the challenge. How does the computer's brain work?. Artificial intelligence. Towards an intelligent computer -- How to Make all that stuff hold together. The challenge is open. How to make man and computer cooperate. How to make man and computer cooperate?. Is transhumanism a realistic future?. A way for brain and computer to work together? -- Conclusion.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat Reader.
Keywords: Neuromorphics; Artificial intelligence; Human-computer interaction; Cognitive science; Electronic books